2014
DOI: 10.1111/sms.12234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of magnetic resonance techniques to measure muscle damage 24 h after eccentric exercise

Abstract: The study examined which of a number of different magnetic resonance (MR) methods were sensitive to detecting muscle damage induced by eccentric exercise. Seventeen healthy, physically active participants, with muscle damage confirmed by non-MR methods were tested 24 h after performing eccentric exercise. Techniques investigated whether damage could be detected within the quadriceps muscle as a whole, and individually within the rectus femoris, vastus lateralis (VL), vastus medialis (VM), and vastus intermediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 53 publications
5
32
2
2
Order By: Relevance
“…It is also worth noting that although muscle damage was evident in this study based on the decreases in maximal torque and RTD as well as occurrence of DOMS, the observed increases in T 2 were relatively small (3–5%). Importantly, these values were within the range of those (3–11%) reported by previous studies 11, 37, 61 on a T 2 change in the KEs following multi-joint eccentric exercises. This suggests that a T 2 response is generally low compared to other muscle damage markers, at least in the leg muscles.…”
Section: Discussionsupporting
confidence: 87%
“…It is also worth noting that although muscle damage was evident in this study based on the decreases in maximal torque and RTD as well as occurrence of DOMS, the observed increases in T 2 were relatively small (3–5%). Importantly, these values were within the range of those (3–11%) reported by previous studies 11, 37, 61 on a T 2 change in the KEs following multi-joint eccentric exercises. This suggests that a T 2 response is generally low compared to other muscle damage markers, at least in the leg muscles.…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, in the same study, multi‐joint ECC squat exercise matched with the former for exercise variables (ie, % load of one repetition maximum, repetitions, sets) did not increase T 2 in RF. These findings are in line with previous studies showing pronounced T 2 increase in RF after single‐joint ECC knee extension exercise and no T 2 increase after squat exercise, indicating that RF is preferentially recruited (or exposed to ECC stimuli) during single‐joint ECC knee extension exercise. Wakahara et al reported that regional differences in a T 2 increase within a muscle group after an acute bout of resistance exercise corresponded to those in the hypertrophy after training (ie, the magnitude of hypertrophy was greater at sites where the acute T 2 increase was pronounced).…”
Section: Introductionsupporting
confidence: 93%
“…T 2 did not change throughout the intervention period in all muscles, even in RF, for both legs (Figure ). Previous studies using the T 2 ‐MRI technique to localize muscle damage following an acute exercise bout had participants perform damaging eccentric exercises (ie, ~10 reps × 5‐10 sets) in an unaccustomed (naive) state to “induce” certain degrees of damage. By contrast, we tried to “avoid” potential muscle damage, which often has negative influences on muscle performances and causes discomfort muscle soreness, by gradually increasing the set numbers at the initial sessions (ie, ~10 reps × 3‐5 sets in the initial 1‐3 sessions).…”
Section: Discussionmentioning
confidence: 99%
“…The three superficial muscle heads exhibited the same behavior at each of the 4 measurement times and exhibited similar changes in μ . Note that the VI muscle, the most solicited muscle with respect to eccentric contraction elicited during downhill running [42], was not assessed because of its depth, which made performing elastographic measurements via ultrasound difficult. It has been established that the magnitudes of the micro-lesions incurred during eccentric solicitation induced by MUMs are dependent on the muscle type, the level of force generated during the period and/or the amplitude of stretching, as well as the duration of exercise [27].…”
Section: Discussionmentioning
confidence: 99%